9. Standard form-2 using Big M method : Example-3
Find solution using Revised Simplex (BigM) method MIN Z = 3x1 + 2x2 + x3 subject to x1 + x2 + x3 >= 4 x2 - x3 <= 2 x1 + x2 + 2x3 = 6 and x1,x2,x3 >= 0
Solution: Problem is
Min `Z` | `=` | `` | `3` | `x_1` | ` + ` | `2` | `x_2` | ` + ` | `` | `x_3` |
| subject to | `` | `` | `x_1` | ` + ` | `` | `x_2` | ` + ` | `` | `x_3` | ≥ | `4` | | | | `` | `` | `x_2` | ` - ` | `` | `x_3` | ≤ | `2` | `` | `` | `x_1` | ` + ` | `` | `x_2` | ` + ` | `2` | `x_3` | = | `6` |
| and `x_1,x_2,x_3 >= 0; ` |
`:.` Max `Z` | `=` | ` - ` | `3` | `x_1` | ` - ` | `2` | `x_2` | ` - ` | `` | `x_3` |
Step-1 : The problem is converted to canonical form by adding slack, surplus and artificial variables as appropiate
After introducing slack,surplus,artificial variables
`` | `` | `x_1` | ` + ` | `` | `x_2` | ` + ` | `` | `x_3` | ` - ` | `` | `S_1` | | | | ` + ` | `` | `A_1` | | | | = | `4` | | | | `` | `` | `x_2` | ` - ` | `` | `x_3` | | | | ` + ` | `` | `S_2` | | | | | | | = | `2` | `` | `` | `x_1` | ` + ` | `` | `x_2` | ` + ` | `2` | `x_3` | | | | | | | | | | ` + ` | `` | `A_2` | = | `6` |
|
The problem is converted to canonical form by adding slack, surplus and artificial variables as appropiate
After introducing slack,surplus,artificial variables
`` | `` | `Z'` | ` + ` | `3` | `x_1` | ` + ` | `2` | `x_2` | ` + ` | `` | `x_3` | | | | | | | ` - ` | `M` | `A_1` | ` - ` | `M` | `A_2` | = | `0` | | | | `` | `` | `x_1` | ` + ` | `` | `x_2` | ` + ` | `` | `x_3` | ` - ` | `` | `S_1` | | | | ` + ` | `` | `A_1` | | | | = | `4` | | | | | | | `` | `` | `x_2` | ` - ` | `` | `x_3` | | | | ` + ` | `` | `S_2` | | | | | | | = | `2` | | | | `` | `` | `x_1` | ` + ` | `` | `x_2` | ` + ` | `2` | `x_3` | | | | | | | | | | ` + ` | `` | `A_2` | = | `6` |
|
Now represent the new system of constraint equations in the matrix form `[[1,3,2,1,0,0,-M,-M],[0,1,1,1,-1,0,1,0],[0,0,1,-1,0,1,0,0],[0,1,1,2,0,0,0,1]][[Z'],[x_1],[x_2],[x_3],[S_1],[S_2],[A_1],[A_2]]=[[0],[4],[2],[6]]`
or `[[1,-c],[0,A]][[Z],[x]]=[[0,b]]; x>=0`
where `e=beta_0,a_4=beta_1,a_5=beta_2,a_6=beta_3`
Step-2 : The basis matrix `B_1` of order `(3+1)=4` can be expressed as
`B_1=[beta_0,beta_1,beta_2,beta_3]=[[1,-M,0,-M],[0,1,0,0],[0,0,1,0],[0,0,0,1]]`
Then, `B_1^(-1)=[[1,C_B B^(-1)],[0,B^(-1)]]=1; B=[[1,0,0],[0,1,0],[0,0,1]]=[beta_1,beta_2,beta_3]; C_B=[0,0,0]`
| | Basis Inverse `B_1^(-1)` | | | Additional table | `B` | `X_B` | `beta_0` `Z'` | `beta_1` `A_1` | `beta_2` `S_2` | `beta_3` `A_2` | `y_1` | Min Ratio `(X_B)/(y_1)` | `x_1` | `x_2` | `x_3` | `S_1` | `Z'` | `0` | `1` | `-M` | `0` | `-M` | | --- | `3` | `2` | `1` | `0` | `A_1` | `4` | `0` | `1` | `0` | `0` | | --- | `1` | `1` | `1` | `-1` | `S_2` | `2` | `0` | `0` | `1` | `0` | | --- | `0` | `1` | `-1` | `0` | `A_2` | `6` | `0` | `0` | `0` | `1` | | --- | `1` | `1` | `2` | `0` |
Iteration=1 : Repeat steps 3 to 5 to get new solution Step-3: To select the vector corresponding to a non-basic variable to enter into the basis, we compute `z_k-c_k="Min" {(z_j-c_j)<0;}`
`="Min"{(1^(st)" row of " B_1^(-1)) ("Columns " a_j " not in basis")}`
`="Min"{[[1,-M,0,-M]] [[3,2,1,0],[1,1,1,-1],[0,1,-1,0],[1,1,2,0]]}`
`="Min"{[[-2M+3,-2M+2,-3M+1,M]]}`
`=-3M+1` (correspnds to `z_3-c_3`)
Thus, vector `x_3` is selected to enter into the basis, for `k=3`
Step-4: To select a basic variable to leave the basis, we compute `y_k` for k=3, as follows
`y_3= B_1^(-1) a_3=[[1,-M,0,-M],[0,1,0,0],[0,0,1,0],[0,0,0,1]] [[1],[1],[-1],[2]]=[[-3M+1],[1],[-1],[2]]`
and `X_B = [[0],[4],[2],[6]]`
Now, calculate the minimum ratio to select the basic variable to leave the basis `x_(Br)/y_(rk)= "Min" {x_(Bi)/y_(ik), y_(ik)>0}`
`="Min"{(4)/(1),(6)/(2)}`
`="Min"{4,3}`
`=3 ("correspnds to " x_(B3)/y_(33))`
Thus, vector `A_2` is selected to leave the basis, for `r=3`
The table with new entries in column `y_3` and the minimum ratio
| | Basis Inverse `B_1^(-1)` | | | Additional table | `B` | `X_B` | `beta_0` `Z'` | `beta_1` `A_1` | `beta_2` `S_2` | `beta_3` `A_2` | `y_3` | Min Ratio `(X_B)/(y_3)` | `x_1` | `x_2` | `x_3` | `S_1` | `Z'` | `0` | `1` | `-M` | `0` | `-M` | `-3M+1` | --- | `3` | `2` | `1` | `0` | `A_1` | `4` | `0` | `1` | `0` | `0` | `1` | `4` | `1` | `1` | `1` | `-1` | `S_2` | `2` | `0` | `0` | `1` | `0` | `-1` | --- | `0` | `1` | `-1` | `0` | `A_2` | `6` | `0` | `0` | `0` | `1` | `2` | `3` | `1` | `1` | `2` | `0` |
The table solution is now updated by replacing variable `A_2` with the variable `x_3` into the basis.
For this we apply the following row operations in the same way as in the simplex method
| `X_B` | `beta_1` | `beta_2` | `beta_3` | `y_3` | `R_1` | `0` | `-M` | `0` | `-M` | `-3M+1` | `R_2` | `4` | `1` | `0` | `0` | `1` | `R_3` | `2` | `0` | `1` | `0` | `-1` | `R_4` | `6` | `0` | `0` | `1` | `2` |
`R_4`(new)`= R_4`(old)` -: 2``R_4`(old) = | `6` | | `0` | `0` | `1` | `R_4`(new)`= R_4`(old)` -: 2` | `3` | | `0` | `0` | `1/2` |
`R_1`(new)`= R_1`(old) + `(3M-1) R_4`(new)`R_1`(old) = | `0` | | `-M` | `0` | `-M` | `R_4`(new) = | `3` | | `0` | `0` | `1/2` | `3M-1 xx R_4`(new) = | `9M-3` | | `0` | `0` | `(3M-1)/2` | `R_1`(new)`= R_1`(old) + `(3M-1) R_4`(new) | `9M-3` | | `-M` | `0` | `(M-1)/2` |
`R_2`(new)`= R_2`(old) - `R_4`(new)`R_2`(old) = | `4` | | `1` | `0` | `0` | `R_4`(new) = | `3` | | `0` | `0` | `1/2` | `R_2`(new)`= R_2`(old) - `R_4`(new) | `1` | | `1` | `0` | `-1/2` |
`R_3`(new)`= R_3`(old) + `R_4`(new)`R_3`(old) = | `2` | | `0` | `1` | `0` | `R_4`(new) = | `3` | | `0` | `0` | `1/2` | `R_3`(new)`= R_3`(old) + `R_4`(new) | `5` | | `0` | `1` | `1/2` |
The improved solution is
| | Basis Inverse `B_1^(-1)` | | | Additional table | `B` | `X_B` | `beta_0` `Z'` | `beta_1` `A_1` | `beta_2` `S_2` | `beta_3` `x_3` | `y_3` | Min Ratio `(X_B)/(y_3)` | `x_1` | `x_2` | `A_2` | `S_1` | `Z'` | `9M-3` | `1` | `-M` | `0` | `(M-1)/2` | | --- | `3` | `2` | `M` | `0` | `A_1` | `1` | `0` | `1` | `0` | `-1/2` | | --- | `1` | `1` | `0` | `-1` | `S_2` | `5` | `0` | `0` | `1` | `1/2` | | --- | `0` | `1` | `0` | `0` | `x_3` | `3` | `0` | `0` | `0` | `1/2` | | --- | `1` | `1` | `1` | `0` |
Iteration=2 : Repeat steps 3 to 5 to get new solution Step-3: To select the vector corresponding to a non-basic variable to enter into the basis, we compute `z_k-c_k="Min" {(z_j-c_j)<0;}`
`="Min"{(1^(st)" row of " B_1^(-1)) ("Columns " a_j " not in basis")}`
`="Min"{[[1,-M,0,(M-1)/2]] [[3,2,M,0],[1,1,0,-1],[0,1,0,0],[1,1,1,0]]}`
`="Min"{[[(-M+5)/2,(-M+3)/2,(3M-1)/2,M]]}`
`=(-M+3)/2` (correspnds to `z_2-c_2`)
Thus, vector `x_2` is selected to enter into the basis, for `k=2`
Step-4: To select a basic variable to leave the basis, we compute `y_k` for k=2, as follows
`y_2= B_1^(-1) a_2=[[1,-M,0,(M-1)/2],[0,1,0,-1/2],[0,0,1,1/2],[0,0,0,1/2]] [[2],[1],[1],[1]]=[[(-M+3)/2],[1/2],[3/2],[1/2]]`
and `X_B = [[9M-3],[1],[5],[3]]`
Now, calculate the minimum ratio to select the basic variable to leave the basis `x_(Br)/y_(rk)= "Min" {x_(Bi)/y_(ik), y_(ik)>0}`
`="Min"{(1)/(1/2),(5)/(3/2),(3)/(1/2)}`
`="Min"{2,10/3,6}`
`=2 ("correspnds to " x_(B1)/y_(12))`
Thus, vector `A_1` is selected to leave the basis, for `r=1`
The table with new entries in column `y_2` and the minimum ratio
| | Basis Inverse `B_1^(-1)` | | | Additional table | `B` | `X_B` | `beta_0` `Z'` | `beta_1` `A_1` | `beta_2` `S_2` | `beta_3` `x_3` | `y_2` | Min Ratio `(X_B)/(y_2)` | `x_1` | `x_2` | `A_2` | `S_1` | `Z'` | `9M-3` | `1` | `-M` | `0` | `(M-1)/2` | `(-M+3)/2` | --- | `3` | `2` | `M` | `0` | `A_1` | `1` | `0` | `1` | `0` | `-1/2` | `1/2` | `2` | `1` | `1` | `0` | `-1` | `S_2` | `5` | `0` | `0` | `1` | `1/2` | `3/2` | `10/3` | `0` | `1` | `0` | `0` | `x_3` | `3` | `0` | `0` | `0` | `1/2` | `1/2` | `6` | `1` | `1` | `1` | `0` |
The table solution is now updated by replacing variable `A_1` with the variable `x_2` into the basis.
For this we apply the following row operations in the same way as in the simplex method
| `X_B` | `beta_1` | `beta_2` | `beta_3` | `y_2` | `R_1` | `9M-3` | `-M` | `0` | `(M-1)/2` | `(-M+3)/2` | `R_2` | `1` | `1` | `0` | `-1/2` | `1/2` | `R_3` | `5` | `0` | `1` | `1/2` | `3/2` | `R_4` | `3` | `0` | `0` | `1/2` | `1/2` |
`R_2`(new)`= R_2`(old) `xx2``R_2`(old) = | `1` | | `1` | `0` | `-1/2` | `R_2`(new)`= R_2`(old) `xx2` | `2` | | `2` | `0` | `-1` |
`R_1`(new)`= R_1`(old) + `((M-3)/2) R_2`(new)`R_1`(old) = | `9M-3` | | `-M` | `0` | `(M-1)/2` | `R_2`(new) = | `2` | | `2` | `0` | `-1` | `(M-3)/2 xx R_2`(new) = | `M-3` | | `M-3` | `0` | `(-M+3)/2` | `R_1`(new)`= R_1`(old) + `((M-3)/2) R_2`(new) | `10M-6` | | `-3` | `0` | `1` |
`R_3`(new)`= R_3`(old) - `3/2 R_2`(new)`R_3`(old) = | `5` | | `0` | `1` | `1/2` | `R_2`(new) = | `2` | | `2` | `0` | `-1` | `3/2 xx R_2`(new) = | `3` | | `3` | `0` | `-3/2` | `R_3`(new)`= R_3`(old) - `3/2 R_2`(new) | `2` | | `-3` | `1` | `2` |
`R_4`(new)`= R_4`(old) - `1/2 R_2`(new)`R_4`(old) = | `3` | | `0` | `0` | `1/2` | `R_2`(new) = | `2` | | `2` | `0` | `-1` | `1/2 xx R_2`(new) = | `1` | | `1` | `0` | `-1/2` | `R_4`(new)`= R_4`(old) - `1/2 R_2`(new) | `2` | | `-1` | `0` | `1` |
The improved solution is
| | Basis Inverse `B_1^(-1)` | | | Additional table | `B` | `X_B` | `beta_0` `Z'` | `beta_1` `x_2` | `beta_2` `S_2` | `beta_3` `x_3` | `y_2` | Min Ratio `(X_B)/(y_2)` | `x_1` | `A_1` | `A_2` | `S_1` | `Z'` | `10M-6` | `1` | `-3` | `0` | `1` | | --- | `3` | `M` | `M` | `0` | `x_2` | `2` | `0` | `2` | `0` | `-1` | | --- | `1` | `1` | `0` | `-1` | `S_2` | `2` | `0` | `-3` | `1` | `2` | | --- | `0` | `0` | `0` | `0` | `x_3` | `2` | `0` | `-1` | `0` | `1` | | --- | `1` | `0` | `1` | `0` |
Iteration=3 : Repeat steps 3 to 5 to get new solution Step-3: To select the vector corresponding to a non-basic variable to enter into the basis, we compute `z_k-c_k="Min" {(z_j-c_j)<0;}`
`="Min"{(1^(st)" row of " B_1^(-1)) ("Columns " a_j " not in basis")}`
`="Min"{[[1,-3,0,1]] [[3,M,M,0],[1,1,0,-1],[0,0,0,0],[1,0,1,0]]}`
`="Min"{[[1,M-3,M+1,3]]}`
Since all `Z_j-C_j >= 0`
Hence, optimal solution is arrived with value of variables as : `x_1=0,x_2=2,x_3=2`
Max `Z=-6`
`:.` Min `Z=6`
This material is intended as a summary. Use your textbook for detail explanation. Any bug, improvement, feedback then
|